Training and Innovation in Public Sector Organizations in Nigeria: A Case Study of Federal Road Safety Sokoto Command - Fatima Ali Suwaid; Ph.D. (International Journal of innovative inventions in Social Science and Humanities, 2026)
This study investigates the relationship between training and innovation in public sector organizations in Nigeria, with a focus on the Federal Road Safety Corps (FRSC) Sokoto Command. A quantitative research approach was employed, with 200 questionnaires distributed to FRSC personnel and 158 valid responses retrieved. The study examines the impact of training on innovation, specifically exploring the effects of training on employee creativity, problem-solving skills, and adoption of new technologies. The results show a significant positive correlation between training and innovation, suggesting that investment in employee training is crucial for driving innovation in public sector organizations.